27 PATTERNS OF ANTICOAGULATION AND MANAGEMENT OF ATRIAL FIBRILLATION BY PRIMARY CARE PROVIDERS IN A GERIATRIC POPULATION. Issue 1 (1st January 2007) - Do, R. Q.; Habibzadeh, M. R.; Fain, M. J.; Goldman, S.
Abstract : Atrial fibrillation is the most common cardiac arrhythmia, and prevalence increases rapidly with age. It occurs in approximately 5% of people over the age of 65 and in 10% of people over 80 years old. Atrial fibrillation is clinically significant in that it can be associated with decreased cardiac output and is also associated with a high risk of systemic embolism. One of the most recognized and devastating complications is stroke, with percentage rates increasing per year in this arrhythmia. In fact, stroke risk is estimated to be 50 times higher in a patient over 85 years old than in someone aged 50 years. Warfarin sodium for anticoagulation has been found to decrease the risk of stroke by 62%, whereas aspirin decreases risk by 22%. Most studies involving atrial fibrillation and anticoagulation have been performed on patients younger than 80 years old. Studies have demonstrated that only 15 to 44% of patients with atrial fibrillation are anticoagulated even if there has been shown to be benefit from anticoagulation. Additionally, the elderly are least likely to be anticoagulated, although their risk of stroke is much higher than in younger patients. This may be due to patient and provider preferences, along with benefit-risk ratios as yet to be formally defined. Currently, recommendations from the ACC/AHA/ESC regarding anticoagulation are based on risk stratification, of which age and anticoagulation intensity are the only factors formally defined. Therefore, this study seeks to define practice patterns of atrial fibrillation management in VA primary care settings as they compare with current guidelines. Patients admitted to the VAMC Home Based Primary Care Program were evaluated, with approximately 80 carrying the diagnosis of atrial fibrillation. This diagnosis was adjudicated with ECGs, Holter monitors, or echocardiograms. Practice patterns involving rate controlling agents, anticoagulation, and laboratory monitoring were studied. If patients were not anticoagulated, reasons for deferring this therapy were explored through extensive chart review. As few studies exist regarding anticoagulation and AF management in the elderly, this study can provide more background for future geriatric cardiovascular research. The goal of this study is to analyze the practice patterns of primary care physicians to further improve evaluation and treatment of atrial fibrillation as recommended by current practice guidelines. Knowing how our practices measure up to current guidelines will increase awareness among physicians and help us identify how perceived contraindications for anticoagulation affect our practice.